ANALISIS MAKNA BAHASA FIGURATIF DALAM LIRIK LAGU ANTI-HERO KARYA TAYLOR SWIFT - Diva Azka Layalia; Abdul Muntaqim Al Anshory (Haluan Sastra Budaya, 2023)
Analyzing the meaning of expressions containing figurative language is unique, especially when analyzing song lyrics. Every Individual, especially songwriters have their own language in expressing the message they want to convey. The purpose of this research is to classify and analyze the meaning of Taylor Swift's Anti-Hero song lyrics based on phrases that contain figurative language. This research uses qualitative method with figurative language theory approach proposed by Kennedy & Gioia (2000) which is explained descriptively. The research data source is Anti-Hero song lyrics. The results of the analysis show that the researcher found 13 data; 7 data from the comparative figurative language, metaphor (5 data) and simile (2 data), 4 data from the contradictory figurative language, hyperbole (3 data) and paradox (1 data), and 2 data from the correlative figurative language, metonymy (1 data) and symbol (1 data). Songwriters try to express feelings or ideas imaginatively in song lyrics that use figurative language. With this, song lyrics can create a special image in expressing one's emotions.